Implementasi Program Penguatan Keagamaan dan Dampaknya terhadap Kecerdasan Spiritual Siswa di SMP Negeri 5 Sinunukan : Penelitian - Tini Melinda Nst; Martin Kustati; Nana Sepriyanti (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The researcher aims to expand the intervention program of SMP Negeri 05 Sinunukan to improve psychosocial risk factors. The methods used in the first study were a qualitative mix of qualitative data collection, analysis, and writing. The results of the exhibition program pembinaan keagamaan to work through melalui to work in accordance with the characteristics of shalat berjamaah, mengaji, meriikan nasihat on their apples, how to build the personality of people with a higher level of self-esteem. The positive impact of the program was seen in terms of increasing students' spiritual awareness, as measured by attitudes of tolerance, empathy, discipline, and responsibility in everyday life. Thus, the organization and resources offered to members have an important contribution in the process of spiritual development in college.